2009
DOI: 10.1073/pnas.0904439106
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic snapshots of iterative substrate translocations during nicotianamine synthesis in archaea

Abstract: Nicotianamine (NA), a small molecule ubiquitous in plants, is an important divalent metal chelator and the main precursor of phytosiderophores. Nicotianamine synthase (NAS) is the enzyme catalyzing NA synthesis by the condensation of three aminopropyl moieties of S-adenosylmethionine (SAM) and the cyclization of one of them to form an azetidine ring. Here we report five crystal structures of an archaeal NAS from Methanothermobacter thermautotrophicus, either free or in complex with its product(s) and substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
33
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 33 publications
5
33
1
Order By: Relevance
“…Some studies have demonstrated that microbial NAS are involved in the synthesis of NA‐related molecules that may exhibit species‐specific chemical features. The archeon Methanothermobacter thermautotrophicus synthesizes a molecule denominated thermonicotianamine, deriving from the condensation of two SAM molecules and a glutamic acid residue (Dreyfus et al ., ). This molecule is very similar to NA, but lacks the azetidine ring.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have demonstrated that microbial NAS are involved in the synthesis of NA‐related molecules that may exhibit species‐specific chemical features. The archeon Methanothermobacter thermautotrophicus synthesizes a molecule denominated thermonicotianamine, deriving from the condensation of two SAM molecules and a glutamic acid residue (Dreyfus et al ., ). This molecule is very similar to NA, but lacks the azetidine ring.…”
Section: Discussionmentioning
confidence: 97%
“…We considered the possibility that NAS could incorporate two aminobutyrate moieties as in M. thermautotrophicus 15 or three as in plant NAS enzymes. 18 This would result in neutral product masses of 487.20 and 588.25 Da.…”
mentioning
confidence: 99%
“…Nicotianamine (NA) is a low molecular mass metal chelator molecule with high binding affinity for a range of transition metal cations. It is synthesized enzymatically from three molecules of S-adenosyl Met by NICOTIANAMINE SYNTHASEs (NASs), which have been identified in vascular plants, Neurospora crassa, and Archaea and in silico in the moss Physcomitrella patens that was reported to contain NA (Higuchi et al, 1999;Trampczynska et al, 2006;Rensing et al, 2008;Dreyfus et al, 2009;Erxleben et al, 2012). The potential use of NA as an antihypertensive drug in humans is under study (Shimizu et al, 1999).…”
Section: Introductionmentioning
confidence: 99%